(untitled) (Bangladesh Journal of Neurosurgery, 2022)
Carotid cavernous fistulas (CCF) are abnormal communications inducing shunting of blood between the carotid arterial system and the cavernous sinus (CS), resulting in flow reversal in the veins draining through the CS.1 CCFs can be classified as spontaneous or traumatic according to the etiology and direct or indirect (dural) according to the anatomical features2. The authors have dealt a case of a spontaneous indirect Carotid-Cavernous Fistula in a young male of 30 on the right side. The patient presented with headache and bulging of right eye. On examination there was pulsatile proptosis on the right side with conjunctival congestion. CT angiography revealed CCF on the right side with dilated, tortuous right ophthalmic and common facial vein. DSA revealed indirect Carotid-Cavernous Fistula fed by right middle meningeal artery (MMA), accessory meningeal artery and branch of right ophthalmic artery(OA) drained by right ophthalmic vein with abnormal communication via right common facial vein. Patient underwent transarterial embolization with ONYXR . DSA revealed total obliteration of fistula. Headache subsided and proptosis reduced immediately after embolization on procedure table with intact neurology. Almost two months down the follow up revealed complete recovery of proptosis and conjunctival congestion with no further headache. Bang. J Neurosurgery 2022; 11(2): 128-133